A biomass fiber adsorbent grafted with phosphate/amidoxime for efficient extraction of uranium from seawater by synergistic effect. (1st July 2023) - Ye, Xiaoxia; Chi, Ruiyang; Wu, Zhihao; Chen, Jinteng; Lv, Yuancai; Lin, Chunxiang; Liu, Yifan; Luo, Wei
Abstract: There are approximately 4 billion tons of uranium in the ocean, which is unmatched by the surface. Nevertheless, it's very challenging to extract uranium from the ocean due to the exceedingly low concentration of uranium in the ocean (about 3.3 μg L −1 ) as well as high salinity level. Current methods are often limited by selectivity, sustainability, economics, etc. Herein, phosphoric acid group and amidoxime group were grafted to skin collagen fibers through " initiated access" to design a new uranium extraction material, abbreviated as CGPA. Through laboratory simulation experiments, it is concluded that the maximum adsorption capacity of CGPA for uranium reaches 263.86 mg g −1 . It has high adsorption, selectivity, and reusability for uranium. In the actual seawater extraction experiment, CGPA obtained 29.64 μg of uranium after extracting 10.0 L of seawater, and the extraction rate was 90.1%. The adsorbent has excellent effects in kinetics, selectivity, extraction capacity, renewability, etc. In the extraction of uranium from seawater, and is an economically feasible and industrially expandable adsorbent. Graphical abstract: Image 1 Highlights: Phosphate and amidoxime were used for uranium extraction by synergistic effect. The CGPA is capable of selectively adsorbing uranium with exceptional capacity. The uranium extraction mass of CGPA is 29.64 μg with extraction rate of 90.1%. CGPA has high extraction rate and selectivity for uranium in seawater.